GE_GERICHTE A/4730/2005 vom 19. Mai 2008 - GE Cour de justice (2008)
; CONDITION DE RECEVABILITÉ ; CONCLUSIONS ; VALEUR LOCATIVE ; DÉDUCTION POUR FRAIS D'ENTRETIEN D'IMMEUBLE | LPFisc.39; LPFisc.50.al.2; LPFisc.51; LPFisc.49.al.2; LIPP-IV.7.al.1; LIPP-V.6.al.4